PREFERENSI MAHASISWA TERHADAP PROGRAM PENDIDIKAN POFESI GURU (PPG): MATERI DAN STRATEGI DIKLAT - Ali Ajam; Safrudin Sahmadan (EDUKASI, 2022)
This study aims at investigate the preference of teachers professional education program (PP) students toward the effectiveness of the PPG program. The effectiveness and the appropriateness were assessed in two variables, namely the material and the strategy given. This research applied qualitative descriptive design by involved 100 students as the sample. Furthermore, the data was collected through Questionnaire in bases from Google Form-based survey which was adopted from PPG Program Evaluation questionnaire from the Ministry of Education. This study found that 80% and 13% of alumni said that the PPG content such as neither the material nor the strategy were in line with the needs of pre- service English teachers. In sum, from the result, it could be outlined that as many as 93% students satisfied with the Teacher Professional Education Program. Therefore, the program of Teacher Professional Education could be assumed had positive impact.